2018
DOI: 10.1002/14651858.cd011005.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of fatigue in amyotrophic lateral sclerosis/motor neuron disease

Abstract: It is impossible to draw firm conclusions about the effectiveness of interventions to improve fatigue for people with ALS/MND as there are few randomised studies, and the quality of available evidence is very low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 50 publications
0
46
1
3
Order By: Relevance
“…However, standardized treatment for fatigue in PD patients does exist, inclusive of a balanced medication regime targeting movement disorder (e.g., dopaminergic agents) and depression (e.g., psychostimulants and antidepressants) combined with a rehabilitation program (e.g., cognitive behavior therapy and graded exercise) (5). Furthermore, research has demonstrated that pharmacological (modafinil) and non-pharmacological (respiratory exercise and repetitive transcranial magnetic stimulation) management may be possible treatment options for fatigue in ALS patients (43). These reports indicate that the appropriate combination of pharmacological and nonpharmacological treatments could be promising treatment options for alleviating fatigue and the severity of ataxia in SCA3 patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, standardized treatment for fatigue in PD patients does exist, inclusive of a balanced medication regime targeting movement disorder (e.g., dopaminergic agents) and depression (e.g., psychostimulants and antidepressants) combined with a rehabilitation program (e.g., cognitive behavior therapy and graded exercise) (5). Furthermore, research has demonstrated that pharmacological (modafinil) and non-pharmacological (respiratory exercise and repetitive transcranial magnetic stimulation) management may be possible treatment options for fatigue in ALS patients (43). These reports indicate that the appropriate combination of pharmacological and nonpharmacological treatments could be promising treatment options for alleviating fatigue and the severity of ataxia in SCA3 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Pain appears to continue to be an uncontrolled symptom for many PALS, in keeping with prior studies suggesting this is an under recognized and undertreated symptom (24)(25)(26). Fatigue was also noted by a large percentage of caregivers and PALS and available treatments for this symptom are limited and of unclear efficacy (27,28). Quality of life assessment instruments exist which incorporate evaluation of these diverse, impactful symptoms (29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey-study in patients with ALS report that fatigue is the most prevalent impairment and at the same time the least treated [ 35 ]. There is, unfortunately, not enough evidence to make conclusions about effectiveness of pharmacological or non-pharmacological treatments [ 36 ]. Thus, high-quality studies on intervention to improve fatigue in ALS are much needed.…”
Section: Discussionmentioning
confidence: 99%